2003
DOI: 10.1007/s00223-001-1131-x
|View full text |Cite
|
Sign up to set email alerts
|

Dose Related Association of Impact Activity and Bone Mineral Density in Pre-pubertal Girls

Abstract: Impact activity is an important contributor to bone accrual. Children engaging in such activity have been shown to have greater bone mineral density (BMD) than their peers. This cross-sectional study was designed to quantify the association between BMD and impact activity in pre-pubescent girls, specifically examining for a dose-dependent relationship. Fifty 7-11-year-old Caucasian female gymnasts were grouped by hours of gymnastics participation during a 6-month period: LOW, 1-8 hours/week (hrs/wk); HIGH, >8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 38 publications
4
51
1
2
Order By: Relevance
“…Many studies have identified higher aBMD in gymnasts than non-gymnasts at the forearm and other weight-bearing sites (15)(16)(17)(18)(19)(20); only one has explored the relative contributions of geometry and volumetric density (11). Previous analyses by our group demonstrated significantly higher areal BMD at the forearm in premenarcheal gymnasts relative to maturitymatched non-gymnasts; these differences persisted after adjustment for age, height and total body FFM (15).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Many studies have identified higher aBMD in gymnasts than non-gymnasts at the forearm and other weight-bearing sites (15)(16)(17)(18)(19)(20); only one has explored the relative contributions of geometry and volumetric density (11). Previous analyses by our group demonstrated significantly higher areal BMD at the forearm in premenarcheal gymnasts relative to maturitymatched non-gymnasts; these differences persisted after adjustment for age, height and total body FFM (15).…”
Section: Introductionmentioning
confidence: 64%
“…Non-Caucasian subjects were excluded from analyses, as there were insufficient numbers to account for racial variation. Gymnasts were included if they trained for at least 6 hours per week (hrs/wk) in the 2-year period prior to measurement, based upon a previous study (16). Following these criteria, 28 gymnasts and 28 non-gymnasts were evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a relationship between greater muscle power and higher bone density in adolescent gymnasts has been described [17]. Few studies have directly assessed true measures of muscle function in combination with bone strength in young non-elite gymnasts [8,9]. The extent to which non-elite level participation in gymnastics influences upper body musculoskeletal health is under researched.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have assessed the effects of non-elite gymnastics on bone mineral density [7][8][9][10]. Despite reports of significant skeletal benefits, there was a reliance on dual-energy X-ray absorptiometry (DXA) to assess areal bone density.…”
Section: Introductionmentioning
confidence: 99%
“…(28,29) Physical activity and body composition are important determinants of bone mass, geometry, and strength of the femoral neck. (30)(31)(32)(33)(34) It is reasonable to assume that mechanisms connecting physical activity and body composition to bone mass are also linked to structural adaptation, that is, redistribution of bone mass. As a weight-bearing bone, the femur is particularly stimulated during locomotion movements that affect different diverse areas of the bone.…”
Section: Discussionmentioning
confidence: 99%